Strategies in Promoting Industrialised Building System (IBS) among Contractors - Jin Jia, Kwang; Ta Wee, Seow; Mohamed, Sulzakimin; Masrom, Md. Asrul Nasid (Research in Management of Technology and Business, 2021)
In Malaysia, the introduction of the Industrialized Building System (IBS) using precast concrete elements has been implemented since1966, when the government launched two projects involving the construction of Jalan Pekeliling, Kuala Lumpur and Jalan Rifle Range in Penang. Effective construction operation, higher efficiency, cost savings, reduction of foreign labour, quicker and better quality control of construction are the main advantages of IBS. However, over the course of 54 years, the implementation of IBS in Malaysia was just 30% of the private project. The objective of the research is therefore to investigate the level of understanding of IBS among contractors. In addition, other research goals, such as the review of strategies to promote the IBS framework effectively and the examination of the effectiveness of strategies for the adoption of IBS among contractors. In this study, literature research through reading journals, articles, internet, and academic investigation had been carried out. This research study is necessary to develop the strategies of enhancing the adoption of IBS among contractors. The data were analysed by both qualitative and quantitative method. Interview and questionnaires were used for data collection purpose. The qualitative results were analysed by listing out the respondent’s answer while the quantitative results were analysed via SPSS There are 40 respondents from questionnaire and 19 respondents from interview question. The level of understanding of IBS profesionals are high.Life Cycle Cost (LCC) are the most effective method that found in this research.